Modeling the dynamic linkages between agriculture, electricity consumption, income and pollutant emissions for southeastern europe - Satrovic, Elma; Abul, Sadeq J.; Al-Kandari, Ahmad; Satrovıc, Elma (HARD Publishing Company, 2022)
This article investigated the short and long-run relationships between pollutant emissions, income, electricity consumption, and the value added by agriculture, forestry, and fishing by applying the agriculture-induced environmental Kuznets curve hypothesis to Southeastern Europe (SEE) countries from 1996 to 2016. The article’s findings support the evidence of an agriculture-induced environmental Kuznets curve phenomenon in the long-run using the panel autoregressive distributed lag (ARDL) of the pooled mean group (PMG) and fully modified ordinary least square (FMOLS). The short-run findings evidence the legitimacy of an agriculture-induced environmental Kuznets curve phenomenon for Bosnia and Herzegovina, Croatia, Moldova, and Turkey. The bidirectional causality between pollutant emissions and electricity and pollutant emissions and agriculture is confirmed. Moreover, a unidirectional causality is found between income and pollutant emissions. Our results, by revealing the positive inelastic impact of agriculture on pollutant emissions, suggest that greater agricultural production increases electricity consumption and thus leads to higher carbon emissions in SEE countries, calling into dispute the sustainability of agriculture-driven growth. © 2022, HARD Publishing Company. All rights reserved.
Keywords: agriculture; electricity consumption; environmental Kuznets curve; southeastern europe